Sonication-Assisted Mitsunobu Etherification of Sterically Encumbered and Intramolecular Hydrogen Demanding Compounds: A Model towards Intramolecular MPV Reduction - Reinner I Lerrick (IPTEK Journal of Proceedings Series, 2017)
A steric and intramolecular hydrogen bonding controlled substrates has been successfully etherified towards sonication assisted Mitsunobu reaction. This modified alcohol-alcohol coupling reaction of 2-hydroxyacetophenone, substituted 2-hydroxyecetophenone, benzophenone and substituted benzophenones with (2R,4R)-pentanediol was found to be substrate electronic restraint